Defects in the statistical accounting of patients with tuberculosis with its multidrug-resistant pathogen - V. B. Galkin (Туберкулез и болезни лёгких)
In Russia, the accounting of tuberculosis, including multidrug-resistant tuberculosis, is intricate and contains a great deal of data allowing for different interpretation. The modifications of existing forms engender numerous defects in filing them out, which drastically reduces the validity of analytical information and levels off a positive effect off when obtaining additional information. The existing federal statistical tuberculosis reporting forms need modification and adequate and instructional support. The tracking (cohort) follow-up and monitoring system-based methodological approaches to federal and branch reporting require unification. A unified electronic register of tuberculosis patients must serve as a source of additional information.